2008
DOI: 10.1111/j.1753-4887.2005.tb00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Government-Industry Partnership in Weekly Iron-Folic Acid Supplementation for Women of Reproductive Age in the Philippines: Impact on Iron Status

Abstract: The effectiveness of weekly iron-folic acid supplements promoted through a government-industry partnership was assessed in pregnant and non-pregnant women in the Philippines. Compliance to both weekly and daily supplementation increased during the yearlong study period, but was highest with weekly supplementation. Serum ferritin and hematocrit increased significantly, whereas the hemoglobin level showed minimal change, probably because of lack of other heme-forming nutrients such as vitamin A. Serum ferritin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Careful examination of these studies resulted in the inclusion of 45 articles 20,23–66 most of which were based on observational studies (Table 1). The main reasons for excluding articles after completing abstraction were: (i) the intervention and/or exposure occurred after 12 weeks gestation, 67–74 (ii) missing our outcomes of interest, 75–83 and (iii) did not measure periconceptional exposures 84,85 …”
Section: Resultsmentioning
confidence: 99%
“…Careful examination of these studies resulted in the inclusion of 45 articles 20,23–66 most of which were based on observational studies (Table 1). The main reasons for excluding articles after completing abstraction were: (i) the intervention and/or exposure occurred after 12 weeks gestation, 67–74 (ii) missing our outcomes of interest, 75–83 and (iii) did not measure periconceptional exposures 84,85 …”
Section: Resultsmentioning
confidence: 99%
“…In Vietnam, mean Hb levels increased by 6.0 g/L in a cohort of non-pregnant women tested four times over twelve months [ 32 ]. In Cambodia increases in Hb levels were associated with higher socio-economic status in groups of schoolgirls, garment factory workers and rural women [ 33 ], and in the Philippines there was a significant increase in serum ferritin but minimal change in Hb [ 34 ]. Dwivedi et al (2006) reported a Government-sponsored community-based WIFS program targeted at adolescent girls in 13 Indian states.…”
Section: Discussionmentioning
confidence: 99%
“…Berger et al [ 205 ] tested a weekly combined iron-folic acid intervention in the preconception period among Vietnamese women and similarly found the supplementation significantly improved iron status and reduced anemia when compared to baseline. In the Philippines ferritin levels improved, however hemoglobin lagged behind, possibly due to women being deficient in other micronutrients related to heme formation which were not supplemented during the study [ 206 ]. The results of these interventions on a national level were similar to a previous randomized-controlled trial in Bangladesh [ 207 ] where iron-folic acid given as a powdered supplement added to food decreased anemia among non-pregnant women; however this benefit did not extend to those women who became pregnant.…”
Section: Nutritional Interventionsmentioning
confidence: 99%